2022
DOI: 10.1002/pro.4394
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐steady‐state kinetics and solvent isotope effects support the “billiard‐type” transport mechanism in Na+‐translocating pyrophosphatase

Abstract: Membrane‐bound pyrophosphatase (mPPase) found in microbes and plants is a membrane H+ pump that transports the H+ ion generated in coupled pyrophosphate hydrolysis out of the cytoplasm. Certain bacterial and archaeal mPPases can in parallel transport Na+ via a hypothetical “billiard‐type” mechanism, also involving the hydrolysis‐generated proton. Here, we present the functional evidence supporting this coupling mechanism. Rapid‐quench and pulse‐chase measurements with [32P]pyrophosphate indicated that the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…Alternatively, the EPP → EPP* conversion may be rate-limiting and all subsequent steps, including bound PP i breakdown, be much faster. Both alternatives are consistent with the linear pre-steady-state kinetics, but the mechanism with the rate-limiting chemical step is also favored by the high kinetic D/H isotope effect determined by comparing hydrolysis rates in D 2 O and H 2 O [ 23 ].…”
Section: The Coupling Stepmentioning
confidence: 85%
See 4 more Smart Citations
“…Alternatively, the EPP → EPP* conversion may be rate-limiting and all subsequent steps, including bound PP i breakdown, be much faster. Both alternatives are consistent with the linear pre-steady-state kinetics, but the mechanism with the rate-limiting chemical step is also favored by the high kinetic D/H isotope effect determined by comparing hydrolysis rates in D 2 O and H 2 O [ 23 ].…”
Section: The Coupling Stepmentioning
confidence: 85%
“…Accordingly, the two P i s leave the active site as mono-magnesium complexes. Recent pulse-chase measurements of PP i binding to Tm-mPPase have revealed that the reaction sequence additionally involves enzyme isomerization before the hydrolysis step [ 23 ], as in soluble pyrophosphatase [ 24 ]. A corresponding extended variant of the reaction sequence is shown in Scheme 1 B.…”
Section: The Coupling Stepmentioning
confidence: 99%
See 3 more Smart Citations